Development of policy performance indicators to assess the implementation of protection from exposure to secondhand smoke in China. (11th June 2013) - Wan, Xia; Stillman, Frances; Liu, Huilin; Spires, Mark; Dai, Zhen; Tamplin, Stephen; Hu, Daiwei; Samet, Jonathan M; Yang, Gonghuan
Abstract : Objective: To develop an approach for rapid assessment of tobacco control interventions in China. We examined the correlation between components of the Strength of Tobacco Control (SOTC) index and a proposed rapid evaluation indicator, the Policy Performance Indicator (PPI), which is based on protection of non-smokers from secondhand smoke (SHS). The PPI was used to assess the implementation of policies related to SHS at the provincial/municipal level in China. Methods: Stratified random sampling was used to select five types of organisational and household respondents in two municipalities and five provinces in China (Shanghai and Tianjin, Heilongjiang, Henan, Guangdong, Zhejiang and Jiangxi, respectively). Data collection methods included key informant interviews, observation and intercept surveys (organisations), and a modified Global Adult Tobacco Survey (GATS) questionnaire (households). SOTC scores (SHS policy, capacity and efforts), PPI (no smoking in designated smoke-free places) and mid-term to long-term impact (knowledge, attitude and reduced exposure to SHS) were measured, and correlations among them were calculated. Results: The PPI varied across the seven locations. Shanghai led in the component indicators (at 56.5% for indoor workplaces and 49.1% for indoor public places, respectively), followed by Guangdong, Tianjin and Zhejiang (at 30–35% for these two indicators), and finally, Henan and Jiangxi (at 20–25%). Smoke-free policies were more effectively implemented at indoor workplaces than indoor public places. The PPI correlated well with certain components of the SOTC but not with the long-term indicators. Conclusions: The PPI is useful for evaluating implementation of smoke-free policies. As tobacco control programmes are implemented, the PPI offers an indicator to track success and change strategies, without collecting data for a full SOTC index.